Kemampulabaan Perusahaan Sektor Property dan Real Estate: Investigasi Faktor yang Mempengaruhinya - Cahyarani, Ni Putu Eka Nadya; Kusmayadi, Iwan (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2024)
The research explores profitability in property and real estate companies, and thoroughly investigates the influence of working capital turnover, capital structure, and company liquidity. This is an explanatory-research conducted on companies listed on the Indonesia Stock Exchange (IDX) in the property and real estate sector. The sample consists of 14 companies selected through purposive sampling. The research data comprises annual financial reports sourced from secondary data that were publicly available from 2018 to 2022 on the official website of the Indonesia Stock Exchange (www.idx.co.id). Based on panel data regression analysis using model tests with Chow and Hausman tests, the most appropriate model for this research is the Random Effect Model (REM). This research has demonstrated that capital structure, as a significant variable, influences company profitability, while working capital turnover and company liquidity do not have an effect.